Species Identification from Suspected Crocodile Leather Products using Mitochondrial 12S Ribosomal RNA and Cytochrome b Genes - Lee, Haeyong; Kim, Eungsoo; Kim, Hyosook; Jung, Ju Yeon; Kim, Man II; Moon, Seohyun (The Korean Academy of Scientific Criminal Investigation, 2022)
In the forensic field, species identification is important for the strong regulation of illegal wildlife trade. In 2020, Gyeongnam Provicial Police Agency requested a species analysis of smuggling evidences (5 items suspected of crocodile leather: whole leather, shoes, bag, wallets and belt). Herein, we identified species through sequencing of PCR products for mitochondrial 12S ribosomal RNA (12S rRNA) and cytochrome b (Cytb) genes. No PCR products for both genes were obtained from leather samples. In addition, PCR products for both genes were not detected from the outer part of toe bones, toenails, and teeth, located inside the leather. However, we successfully obtained the PCR products for 12S rRNA and Cytb, using DNA extracted from inside of the skull, the presumed blood vessel tissue located inside the jawbone, and inside of the toe bone, toenail, and teeth. The BLAST analysis based on the 12S rRNA and Cytb sequences of specimens showed 100 % homology with Crocodylus siamensis listed on Appendix I of the CITES. Consistently, the neighbor-joining phylogenetic tree constructed using the sample sequences together with sequences of the other crocodile species recovered from NCBI showed 100% sequence similarity with Crocodylus siamensis. Although mitochondrial DNA is useful for species identification in forensics, this case showed that mitochondrial DNA in manufactured leather can be damaged during the tanning process. Thus, it is important to find regions that were not damaged as much as possible by the tanning process KCI Citation Count: 0